ONE HUNDRED DECEASED DONOR LIVER TRANSPLANTATIONS AT A SINGLE CENTER - S.V. Gautier; Y.G. Moysyuk; V.N. Poptsov; M.N. Kornilov; O.M. Tsirulnikova; E.B. Yaroshenko; I.A. Miloserdov; I.V. Pogrebnichenko; L.V. Belskikh (Вестник трансплантологии и искусственных органов)
There’s a report of 100 cadaveric liver transplantation performed from December 2004 to June 2011. Indication for liver transplantation, including retransplantation, technical features of surgery, postoperative complications have been described. Patient survival was significantly lower in HCV-positive and HCC recipient than in other indications. Cumulative recipient survival rate at 1, 3, 5 years is 89; 87; 87%. Cumulative graft survival rate at 1, 3, 5 years is 85; 82; 70%. Long term immunosupression and HCV-infection after transplantation are discussed.